Anaemia in chronic kidney disease - Macdougall, Iain (Henry Stewart Talks, 2016)
Definition of anaemia, Prevalence of anaemia in CKD (renal anaemia), Causes of CKD anaemia, How to treat anaemia in CKD (3 steps of management, iron status and supplementation, ESA therapy), Benefits and harms associated with correction of anaemia, Future of CKD anaemia management (HIF stabilisers)